Pump operations in locally advanced thoracic malignancies - Cicėnas, Saulius; Sirvydis, Vytautas Jonas; Uždavinys, Giedrius; Kalinauskas, Gintaras; Aškinis, Renatas; Zaremba, Sigitas (Acta medica Lituanica, 2013)
Background. The study objective is to evaluate the efficacy of pump operations in locally advanced IIIB (T4N0-1M0) lung cancer and other thoracic malignancies and the results of treatment. Materials and methods. In the period 2003–2011, 6 patients (pts) with locally advanced thoracic malignancies underwent surgery in the Center of Cardiac Surgery of Vilnius University Hospital Santariskiu Clinics (VUH SC). Patients’ characteristics and stage: lung cancer – 3 pts (50.0%), stage IIIB (T4N0-1M0), sarcoma of mediastinum – 2 pts (33.3%), fibrous tumour of mediastinum – 1 pt (16.7%). Patients according to morphology: squamous cell carcinoma – 3 pts (50.0%), neuroangiosarcoma – 1 pt (16.7%), neurosarcoma – 1 pt (16.7%), solitary fibrous tumour – 1 pt (16.7%). After surgery patients received adjuvant treatment: 3 pts with lung cancer received 4 cycles of chemotherapy Gemcitabine with cisplatinum, 2  pts with angiosarcoma received radiation therapy 66 Gy and 6 cycles of chemotherapy Ifosfamide. Results. We performed pneumonectomy with left atrium resection  –  2  pts (33.3%), left pneumonectomy with aorta resection  –  1  pt (16.7%), left atrium resection with left upper lobectomy  –  1  pt (16.7%), mediastinum resection with chest wall reconstruction – 1 pt (16.7%), left pneumonectomy – 1 pt (16.7%). We had no complications after pump operations. Median survival of patients with lung cancer was 2.5 ± 0.5 years, with angiosarcoma 3.5 ± 1.0 years. Five-year survival was 25%. Conclusions. 1. Pump operations are safe and possible in locally advanced thoracic malignancies. 2.  Pump operations and adjuvant treatment may prolong median survival in IIIB (T4N0-1M0) lung cancer patients by 2.5 ± 0.5 years and in angiosarcoma patients by 3.5 ± 1.0 years.
Keywords: pump operations; surgical treatment; thoracic malignancies